Clinical profile of opportunistic infections in HIV seropositive patients attending tertiary centre, Raichur, India - ., Shilpa; Andgi, Aakash (International Journal of Advances in Medicine, 2018)
Background: According to Karnataka state HIV statistics, HIV positivity among general clients tested at ICTCs, Raichur (4.9%) had third highest proportion of HIV positive cases. Authors decided to focus on opportunistic infections (OIs) in HIV patients of Raichur district since they contribute to the mortality and morbidity. Methods: It’s a cross sectional, hospital-based study with 100 patients with HIV infections as per NACO guidelines with features of OIs were included in study. Results: In this study, 77 males (77%), 23 female (23%) patients with 58% (n=58) of them in 30-39yrs age group and 21% (n=21) in 20-29yrs were seen. Majority of cases were laborers (47%) and less educated (n=55). Symptoms included loss of appetite (76%) n=76, fever (72%) n=72, cough (55%) n=55 and diarrhoea15% (n=15). The respiratory system was most frequently involved by opportunistic infections and accounted for 56% (n=56) of the total cases and clinically consolidation/crepitation was most frequent presentation accounting for 75% (n=42). Tuberculosis was most common OI (55%) with combined pulmonary and extra pulmonary in 56.37% (n=31), tubercular meningitis and tubercular lymphadenopathy each accounting for 30.77% (n=12) amounted majority, with pleural effusion 20.52% (n=8). Median CD4+T cell count was 217.72 in TB. Candidiasis is second most common OI with 49% (n=49), median CD4 count being 190.07. Other OIs observed were pneumocystosis 16% (n=16), cryptococcosis 2% (n=2). Conclusions: Most common OI in the study was tuberculosis (in extra pulmonary TB meningitis and TB lymphadenitis) followed by Candidiasis, Pneumocystosis and Cryptococcosis.